Regional Tax Coordination and Foreign Direct Investment - Andreas Haufler; Ian Wooton (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2003)
This paper analyses the effects of a regionally coordinated corporate income tax in a model with three active countries, one of which is not part of the union, and a globally mobile firm. We show that regional tax coordination can lead to two types of welfare gain. First, for investments that would take place in the union in the absence of coordination, a coordinated tax increase can transfer location rents from the firm to the union. Second, by internalising all of the union's benefits from foreign direct investment, a coordinated tax reduction can attract more welfare-enhancing investment than when member states act in isolation. Depending on which motive dominates, tax levels may thus rise or fall under regional coordination.
urn:nbn:de:bvb:19-epub-61-5
Keywords: F15; H73; H87; 330; tax competition; regional coordination; foreign direct investment